TANTANGAN BERBAHASA: ANALISIS KESALAHAN BAHASA PADA PROPOSAL PKM MAHASISWA TEKNIK UNIVERSITAS NEGERI MEDAN - Rozi, Soraya; Kustiawan, Wanda Nur Akila; Syahri, Salwa Khairi Alfi; Aprilliany, Fenny; Chairunnisa, Hera (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
This study analyzes the language errors found in the Student Creativity Program (PKM) Proposal compiled by Engineering students of the State University of Medan (UNIMED). The errors analyzed include aspects of spelling, sentence structure, and the use of words with the affix